THE EFFECT OF SURFACE ROUGHNESS AND STIRRING SPEED ON THE COATING CHARACTERISTICS OF MARTENSITIC ELECTROLESS Ni-P - Rafi Dwi R; Arini Nikitasari; Sunardi Sunardi; Efendi Mabruri (Widyariset, 2018)
Coating process of martensitic stainless steel 420 (SS 420) as the base material component of the steam turbine blade component uses an Electroless Ni-P coating process. This process is one of the solution coatingsthat applied to stainless steel as a substrate to improve corrosion resistance.The goal of this research is to get an idea and information about the effect of surface roughness and stirring speed on the characteristics of Electroless Ni-P layer. Experimental parameters in this research were variations of 0.044 μm, 0.056 μm, 0.101 μm, and 0.164 μm surface roughness and variations of 4.9 rpm, 11.3 rpm, and 21.3 rpm stirring speed. Results showed that the surface roughness and low stiring speed causes the grain distribution becomes more uniform, whichis shown by Scanning Electron Microscopy (SEM) examination. Adhesion layer also increases along with increasing levels of surface roughness. The highest value of adhesion was 1.9 MPa at 0.164 μm and the lowest value of adhesion was 0.8 MPa at 0,044 μm.